4(3x+1)+5(x-3)=

Simple and best practice solution for 4(3x+1)+5(x-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x+1)+5(x-3)= equation:


Simplifying
4(3x + 1) + 5(x + -3) = 0

Reorder the terms:
4(1 + 3x) + 5(x + -3) = 0
(1 * 4 + 3x * 4) + 5(x + -3) = 0
(4 + 12x) + 5(x + -3) = 0

Reorder the terms:
4 + 12x + 5(-3 + x) = 0
4 + 12x + (-3 * 5 + x * 5) = 0
4 + 12x + (-15 + 5x) = 0

Reorder the terms:
4 + -15 + 12x + 5x = 0

Combine like terms: 4 + -15 = -11
-11 + 12x + 5x = 0

Combine like terms: 12x + 5x = 17x
-11 + 17x = 0

Solving
-11 + 17x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 17x = 0 + 11

Combine like terms: -11 + 11 = 0
0 + 17x = 0 + 11
17x = 0 + 11

Combine like terms: 0 + 11 = 11
17x = 11

Divide each side by '17'.
x = 0.6470588235

Simplifying
x = 0.6470588235

See similar equations:

| 166-6x=5x+12 | | 3z-7z=28 | | 4x+12=2x+30 | | w^2-24= | | 8x-6=24 | | -2x^2-4+8x=0 | | 10=x/3+x/7 | | 10=10(y-5)+5y | | -207=1+4(-8v+4) | | 7x-12=3x-16 | | (3a-2b)(3a+3b)=0 | | 6(1-3A)=132 | | 6x-4+2x=28 | | 6(4a+2)=94 | | 6b+10=-14 | | 170-2x=25x+23 | | 3(m+1)+2m=88 | | 2x^2+8y=5x+20 | | 5(8-x)=3x | | -5(6n-4)+2n= | | 3p-3+7p=4p+6 | | 60x=32x | | 60x=26x | | 0.01x+4.74=2.05x-3.42 | | 5*(-2t-3)-(5-(5t+2))=1 | | X^2+8x-xy-8y=0 | | 1/2(4x)=-20 | | 10=15x | | 4x^2-30x+14=0 | | 5x^2-2x=x^2-10x | | 18h*483=462*21h | | 6(3N-1)=-96 |

Equations solver categories